Influence of reservoir construction on surrounding vegetation cover - Liu, Ping; Li, Xinrui; Zhang, Ruikang; Yao, Mengrou; Chen, Junfeng; Li, Yanrong; Jia, Xiangru; Xing, Yunfei (International Journal of Agricultural and Biological Engineering, 2021)
Vegetation is a significant factor in the energy and water cycles. Changes in vegetation are affected by the natural environment and human activities. In this study, the Dalong Reservoir on the Ningyuan River in Sanya, Hainan, was taken as an example to set one type of buffer zone with the reservoir dam site as the center, and two types of horizontal and vertical buffer zones outwards from both banks of the river, and Landsat 5 remote sensing image data and the vegetation data were applied. A coverage estimation model was used to study the temporal and spatial changes in surface vegetation in three types of buffer zones, and the characteristics of the surface vegetation changes in the preterm, midterm and late-term reservoir construction periods were analyzed. The results showed that, (1) During the years of 2000 and 2010, the vegetation coverage first decreased and then increased with time in the scope of the research. During preterm construction (2000-2004), the vegetation coverage in the upstream region decreased while that in the downstream region increased. During midterm construction (2004-2006), the declining rate of vegetation coverage downstream was greater than that upstream, but the influence of reservoir construction on vegetation coverage decreased over time in the late-term construction period (2007-2010); (2) Along the direction of the river length, the vegetation coverage showed a downtrend along with the river flow direction during the whole period (2000-2010), and the influence of reservoir construction on vegetation coverage gradually decreased as the distance from the reservoir increased; (3) Along the direction of the river width, the vegetation coverage in the preterm and midterm construction periods (2000-2006) increased with increasing distance from the riverbanks; (4) The vegetation coverage showed a significant increasing trend with increasing distance from the reservoir. The research results can provide a theoretical reference for reducing the risk of vegetation degradation, strengthening the governance of the ecological environment, and promoting the ecological construction of “landscapes, forests, fields, lakes and grass”.Keywords: reservoir, remote sensing, vegetation coverage, ecological environment, landscapesDOI: 10.25165/j.ijabe.20211403.5344Citation: Liu P, Li X R, Zhang R K, Yao M R, Chen J F, Li Y R, et al. Influence of reservoir construction on surrounding vegetation cover. Int J Agric & Biol Eng, 2021; 14(3): 214–220.